Private games - Patterson, James 1947-; Sullivan, Mark T (New York Grand Central Publishing, 2012)
"Private, the world's most renowned investigation firm, has been commissioned to provide security for the 2012 Olympic games in London. Its agents are the smartest, fastest, and most technologically advanced in the world, and 400 of them have been transferred to London to protect over 10,000 competitors who represent more than 200 countries. The opening ceremony is still hours away when Private investigator and single father of twins, Nigel Steele, is called to the scene of a ruthless murder. A high-ranking member of the games' organizing committee and his mistress have been killed. It's clear that it wasn't a crime of passion, but one of precise calculation and execution. Newspaper reporter Karen Pope receives a letter from a person who calls himself Cronus claiming responsibility for the murders. He also proclaims that he will restore the Olympics to their ancient glory and will destroy all who have corrupted the games with lies, cheating, and greed. Karen immediately hires Private to examine the letter, and she and Nigel uncover a criminal genius who won't stop until he's ended the games for good. "America's #1 storyteller" (Forbes) delivers an exhilarating, action-packed thriller that brings the splendor and emotion of the Olympics to a wildly powerful climax"--
Best selling thriller author
The world's#1 bestselling writer
1
Keywords: FICTION / Thrillers; Private investigators -- Fiction; Private security services -- Fiction; Suspense fiction